Análisis comparativo del efecto cicatrizante de la achupalla (Puya glomerifera) y propóleo aplicado a heridas post-quirúrgicas en caninos - Chango Cunalata, Mayra Elizabeth (2025)
The present research was conducted in the province of Tungurahua, in the parish of Huachi Grande at an altitude of 2,350 meters above sea level, with the following objectives: 1) To determine the chemical composition of achupalla (Puya glomerifera) using mass spectrometry, 2) To assess the effect of its extracts on wound healing in postsurgical wounds, and 3) To evaluate the analgesic effect of achupalla. The study focused on the healing of postoperative wounds in 30 female dogs that underwent ovariohysterectomy, evaluating the efficacy of achupalla and propolis extracts compared to a control group. Most of the subjects were young, between 6 and 11 months old (66.67%), and of low body weight, with 40% ranging from 2 to 7 kg. Wound follow-up over 15 days revealed differentiated healing patterns. Initially (on days 3 and 5), achupalla showed the greatest reduction in wound size. However, from day 7 to the end of the study, propolis demonstrated superior and statistically significant efficacy, achieving the smallest average wound size (0.30 cm) by day 15, compared to achupalla (0.47 cm) and the control group (0.58 cm). This pattern suggests that while achupalla is effective in the early stages, propolis promotes more pronounced and sustained long-term healing. Additionally, postoperative pain was evaluated. On the first day, all dogs experienced intense pain. By the third day, the groups treated with achupalla and propolis showed complete remission to mild pain, while 10% of the control group still exhibited moderate pain. These findings, supported by the cited literature, confirm the potential of both natural extracts, highlighting the superiority of propolis in the advanced phases of tissue regeneration.